Report

jkristen1Follow

Jan. 31, 2023•0 likes•2 views

Jan. 31, 2023•0 likes•2 views

Report

Education

Find an equilibrium solution of the following system: x\' = 3x + 2y - 4 y\' = x + 2y - 7 Solution The system is in equilibrium if x \' = y \' = 0. So it reduces to 3x + 2y = 4 ---------1 x + 2y = 7. --------2 from 1 2y = 4-3x----------3 3 in 2 x+4-3x =7 -2x = 7-4 x = -3/2 Plug this into either equation to get y. 2y = 4-3x 2y = 4 - 3(-3/2) 2y = -1/2 y = -1/4 y = -1/4 ,x = -3/2 .

Based on how the value in some array position i compares to the value.docxjkristen1

BASED ON LABORATORY TESTS- THE FOLLOWING INDEX PROPERTIES HAVE BEEN DE.docxjkristen1

Based on differences in electronegativity- how would you characterize.docxjkristen1

Based on predicted production of 24-000 units- a company anticipates $.docxjkristen1

Based on condensed structural formulas- which of the following compoun.docxjkristen1

Based on HTC corp in 2012- answer these two- each has to be one page e.docxjkristen1

- 1. Find an equilibrium solution of the following system: x' = 3x + 2y - 4 y' = x + 2y - 7 Solution The system is in equilibrium if x ' = y ' = 0. So it reduces to 3x + 2y = 4 ---------1 x + 2y = 7. --------2 from 1 2y = 4-3x----------3
- 2. 3 in 2 x+4-3x =7 -2x = 7-4 x = -3/2 Plug this into either equation to get y. 2y = 4-3x 2y = 4 - 3(-3/2) 2y = -1/2 y = -1/4
- 3. y = -1/4 ,x = -3/2